Self-Image and Economic Behavior - Samahita, Margaret (Department of Economics, Lund University, 2017)
This thesis consists of four papers studying image concerns in three unique settings. The first paper develops a model incorporating self-image into the buyer's utility in a ''Pay-What-You-Want'' (PWYW) pricing scheme. We introduce heterogeneity in consumption utility and image-sensitivity, generating different purchase decisions and optimal prices across individuals. When a good's fixed price is lower than a threshold fair value, PWYW can lead to a lower utility. This may result in a lower purchase rate and higher average price, accounting for previously unexplained field experimental evidence. The second paper presents an analysis of PWYW in competition which explains its entry and limited spread in the market. Sellers choose their pricing schemes sequentially while consumers share their surplus. We show that the profitability and popularity of PWYW depend not only on consumers' preferences, but also on market structure, product characteristics and sellers' strategies. While there is no equilibrium where PWYW dominates the market, given a sufficiently high level of surplus-sharing and product differentiation, it is chosen by the second mover to avoid Bertrand competition. The third paper is motivated by conflicts of self-interests which often lead to expression of emotion to unrelated parties. We study non-instrumental verbal expression in binary ultimatum games, where receivers can comment either privately or to a third-party audience prior to accepting or rejecting the offer. The potential for gossip is sufficient to induce image concerns in senders, resulting in fairer offers in the audience treatment. Consequently, despite insignificant effect on receivers' behavior, the possibility of verbal expression to an audience is found to increase co-operation and hence welfare. There is demand for verbal expression even when it is unobserved or not triggered by negative stimulus. We find no evidence that this is motivated by self-esteem. In the fourth paper, we manipulate the information subjects can share on the web concerning socially sensitive actions (public good contribution) and visibility (selfie) to determine the effect on social image, as captured by the price subjects demand for publication. The overall conclusion from the experiment is that theory about social reputation can predict subjects' social-signaling behavior. People take costly decisions to ''filter'' information about themselves (in retrospect) before it is published. We also report results of a more exploratory nature and find that taking a selfie has a strong negative impact on cooperation among frequent selfie takers, but not on other subjects.
Keywords: self-image; social image; signaling; Pay-What-You-Want; competition; co-operation; communication; selfie